2015
DOI: 10.1021/acs.jpcc.5b06373
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Lithium Polysulfides via Affinitive Interactions: Electrostatic Attraction, Hydrogen Bonding, or in Parallel?

Abstract: Stabilizing lithium polysulfides in cathodes via interactions between polysulfides and affinitive functional groups could prevent polysulfide dissolution, leading to suppressed "shuttle effect" of lithium/sulfur (Li/S) batteries. Herein, four deoxynucleotides (DNs), including A (adenine-DN), T (thymine-DN), G (guanine-DN), and C (cytosine-DN), which own rich polysulfide affinitive groups, are selected to model the anchoring environments of polysulfides. Using the most soluble Li 2 S 8 as probe, our first-princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 58 publications
4
44
0
Order By: Relevance
“…8) in consistent with the literature. 68 The overall Mulliken charges of three nitrogen atoms at a pyrrolic nitrogen doped site were À0.358, À0.418, À0.419, much negative than the pyridinic (three nitrogen atoms with À0.249) and graphitic nitrogen (one nitrogen atom with À0.476), indicating that pyrrolic nitrogen doped site imposed the strongest p-doping effect by withdrawing electrons from the graphene platelet. The isosurface of electron density map is also shown in Fig.…”
Section: 61mentioning
confidence: 96%
“…8) in consistent with the literature. 68 The overall Mulliken charges of three nitrogen atoms at a pyrrolic nitrogen doped site were À0.358, À0.418, À0.419, much negative than the pyridinic (three nitrogen atoms with À0.249) and graphitic nitrogen (one nitrogen atom with À0.476), indicating that pyrrolic nitrogen doped site imposed the strongest p-doping effect by withdrawing electrons from the graphene platelet. The isosurface of electron density map is also shown in Fig.…”
Section: 61mentioning
confidence: 96%
“…Various physical or chemical methods to trap lithium polysulfide have been proposed, [169][170][171] and first-principles methods, again, can provide useful insights on screening effective substrates for polysulfides trapping. Stabilizing lithium polysulfides through the use of affinitive functional groups was explored by Ji et al [172] It was found that the interactions between polysulfides and substrates depend on both electrostatic attraction and hydrogen bonding. [166] The energies are similar in magnitude, although oxygen bonded to vacancies and edges of the graphene substrate has increased binding energy that stabilizes lithium polysulfides on the substrate.…”
Section: The Mechanism Of Lithium Polysulfide Trappingmentioning
confidence: 99%
“…To nd the structures with the minimum energy in S 8 , Li 2 S 8 , Li 2 S 6 and Li 2 S 4 , geometry optimization was carried out to obtain possible linear or closed atomic arrangements. 30,42,43 Fig. 1c shows the stable ground state structures of S 8 and lithium polysuldes.…”
Section: Effect Of Microporous Graphene On Adsorption Of S Speciesmentioning
confidence: 99%